THE COMPARISON OF HEALTH OF CONVENTIONAL COMMERCIAL BANKS AND SHARIA COMMERCIAL BANKS USING THE RGEC METHOD - Desiana, Lidia; Hermailingga, Septi; Manurung, Nancy Eka Putri; Cahya, Gemala (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2023)
This research aims to measure the level of public bank health conventional and Sharia commercial banks with the use RGEC method during the period 2016-2020. The population used in the study This is all commercial banks in Indonesia for the 2016-2020 period registered with the Financial Services Authority. Retrieval technique sample using purposive sampling that obtained consisting of 65 commercial banks of 57 commercial banks conventional and 8 Sharia commercial banks. Study This uses approach descriptive quantitative and research data obtained through technique documentation. The data analysis technique used is statistics descriptive analysis, RGEC analysis, Kolmogorov-Smirnov, Independent Sample T-Test, and Mann Withney U-Test. Research results show that the level of public bank health conventional and Sharia commercial banks in the 2016-2020 period being measured with RGEC method does not own difference because both of them You're welcome to occupy ranking composite 2 with predicate healthy.